A low-alkali cement clinker and a method for producing the same

CN122916468APending Publication Date: 2026-10-16TANGSHAN CHENYUANXIANG TRADING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611253842.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]有鉴于此,本发明的目的在于提出一种低碱水泥熟料及其制备方法,以解决现有低碱熟料难以兼顾低碱含量以及高中后期强度与耐久性能的问题

Benefits of technology

本发明提供的钙硅基功能填料,其核层由硅酸钙经活化处理形成具有丰富硅羟基的活性表面,随后通过分步构筑的方式依次引入第一硅源、第二硅源和酸性硅溶胶,在功能填料表面形成由内向外逐渐过渡的硅羟基梯度层。这种梯度结构使得功能填料在与生料混合后,能够优先吸附并稳定停留在石灰质颗粒与硅质颗粒的接触界面附近,为后续熟料矿物的生成提供了定位精准的反应位点,克服了普通填料在生料中随机分散、难以发挥定向诱导作用的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of cement materials, in particular to a low-alkali cement clinker and a preparation method thereof. The method comprises the following steps: wet grinding calcium silicate, and pre-treating the calcium silicate after activation; then, the pre-treated calcium silicate is sequentially reacted with a first silicon source, a second silicon source, an acidic silicon sol and an ammonium bicarbonate trigger liquid to build a silicon hydroxyl gradient layer on the surface of the pre-treated calcium silicate, so that a calcium-silicon-based functional filler is obtained; then, the functional filler is atomized and sprayed into a pre-wetted low-alkali raw material matrix in the form of a suspension to prepare raw material balls; and finally, the raw material balls are burned and forcedly cooled in stages to obtain the low-alkali cement clinker. The application can improve the burnability of the clinker and reduce the content of free calcium oxide under low-alkali conditions; and the obtained clinker has good early and late strength and good performances of resisting sulfates and resisting seawater erosion after being made into cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement materials technology, specifically to a low-alkali cement clinker and its preparation method. Background Technology

[0002] The production of cement clinker is an energy- and resource-intensive process. Reducing the alkali content (mainly sodium oxide and potassium oxide) in clinker is crucial for improving the long-term durability of concrete. Low-alkali cement can effectively inhibit alkali-aggregate reaction and prevent concrete from cracking due to internal expansion. Therefore, it has irreplaceable application value in major infrastructure projects such as water conservancy projects, bridges and tunnels, and marine structures. However, how to simultaneously achieve good calcination characteristics and stable strength development while ensuring that the clinker alkali content meets the low-alkali requirements remains a technical challenge for the cement industry.

[0003] During the calcination of silicate cement clinker, alkali metal oxides have a strong fluxing effect, reducing the temperature at which the liquid phase appears and the viscosity of the liquid phase. This promotes the decomposition of calcium carbonate and accelerates the conversion of dicalcium silicate (belite) to tricalcium silicate (alite). When low-alkali raw materials are used or the alkali content of the clinker is reduced through technical means, the amount of liquid phase in the calcination system decreases, the temperature at which the liquid phase appears increases, and the viscosity of the liquid phase increases, leading to increased mass transfer resistance and decreased ion migration rate. The most direct consequence of this change is that free calcium oxide in the clinker is difficult to be completely absorbed. Even with extended holding time or increased calcination temperature, free calcium oxide often remains at a high level, seriously affecting the stability and early strength development of cement.

[0004] To address the difficulty of calcination under low alkali conditions, breakthroughs are currently sought primarily in two directions: one is through adjusting the calcinability of raw materials, such as by introducing mineralizers or fluxes to compensate for insufficient liquid phase caused by reduced alkali content. Substances such as calcium fluoride, sodium fluorosilicate, barite, copper slag, and lead-zinc tailings have been attempted as composite mineralizers added to raw materials in order to form a sufficient quantity and suitable viscosity of liquid phase at lower temperatures. However, the amount of mineralizer added needs to be strictly controlled, as excessive introduction may bring new environmental risks or corrosion problems. Furthermore, the synergistic mechanism between different mineralizers is complex, and their adaptability varies greatly in different raw material systems and calcination equipment, making it difficult to form a universal technical solution. Secondly, performance can be optimized through targeted control of clinker mineral composition. For example, by adjusting the lime saturation coefficient, silica ratio, and alumina ratio, the ratio of belite and alite in the clinker can be changed, or more high-temperature crystal forms can be retained through rapid cooling. These methods often focus on adjusting macroscopic proportions and process parameters, and have limited ability to intervene in the microscopic process of mineral crystal growth under low-alkali conditions. Even if the free calcium oxide in the final clinker can meet the standard, the belite crystals are often large and uneven with low activity, and the development of alite crystals is also limited, resulting in insufficient potential for later strength growth of the clinker and reduced resistance to sulfate and seawater erosion. This makes it difficult to meet the requirements of long-term cement performance for marine precast components, underground pipe gallery linings, and foundation engineering in high-sulfate environments.

[0005] Therefore, how to achieve precise control over the growth process of clinker mineral crystals while ensuring that the alkali content meets the low alkali requirements, so that it can simultaneously possess high activity and high stability, remains a technical challenge that urgently needs to be overcome in this field. Summary of the Invention

[0006] In view of this, the purpose of this invention is to propose a low-alkali cement clinker and its preparation method, so as to solve the problem that existing low-alkali clinkers are difficult to balance low alkali content with high and medium late-stage strength and durability.

[0007] To achieve the above objectives, the present invention provides a low-alkali cement clinker, which, by mass parts, is obtained by firing the following raw materials: 770-800 parts calcium carbonate, 130-170 parts quartz powder, 30-40 parts alumina, 20-30 parts iron oxide and 4-7 parts calcium-silicon based functional filler. The calcium-silicon-based functional filler consists of pretreated calcium silicate and a silanol gradient layer coating the surface of the pretreated calcium silicate. Based on 100 parts of the pretreated calcium silicate, the silanol gradient layer is formed by sequentially treating a first silicon source, a second silicon source, an acidic silica sol, and an ammonium bicarbonate trigger solution; the first silicon source is formed by mixing 3.2-4.8 parts of tetraethyl orthosilicate and 12.8-19.2 parts of anhydrous ethanol; the second silicon source is formed by mixing 4.4-5.8 parts of tetraethyl orthosilicate, 0.4-1.0 parts of tetramethoxysilane, 20-26 parts of anhydrous ethanol, and 9-12 parts of a 1% (w / w) aqueous solution of nitric acid; the amount of the acidic silica sol is 16-24 parts; and the amount of the ammonium bicarbonate is 5-8 parts.

[0008] Preferably, the pretreated calcium silicate is obtained by ball milling calcium silicate and then activated by carbonated deionized water. Preferably, the pH value of the carbonated deionized water is 4.0-4.8.

[0009] Preferably, the pH value of the system is maintained at 4.0-5.0 during activation, and the activation time is 18-24 minutes.

[0010] Furthermore, the present invention also provides a method for preparing low-alkali cement clinker, comprising the following steps: (1) Calcium silicate is wet-milled to form pretreated calcium silicate, and the pretreated calcium silicate is dispersed in carbonated deionized water for carbonation activation treatment. After activation, the filter is immediately filtered, washed, and the wet filter cake is retained. (2) Disperse all the wet filter cake obtained in step (1) in a mixed solvent of anhydrous ethanol and deionized water to form a functional filler dispersion slurry; add the first silicon source, the second silicon source and acidic silica sol in sequence, and finally spray in the triggering liquid for aging. After aging, filter, wash, dry and sieve to obtain calcium-silicon based functional filler; (3) Mix calcium carbonate, alumina, iron oxide and quartz powder to obtain a low-alkali raw material matrix; (4) The calcium-silicon-based functional filler is sprayed into the low-alkali raw material matrix in the form of a suspension to form wet raw material, and rolled into raw material balls, which are then dried to obtain raw material balls to be fired. (5) The raw material balls to be fired are heated in stages under an air atmosphere and then forced to cool after firing to obtain low-alkali cement clinker.

[0011] Preferably, the median particle size of the pretreated calcium silicate in step (1) is 2-5 μm.

[0012] Preferably, the pH value of the carbonated deionized water in step (1) is 4.0-4.8.

[0013] Preferably, carbon dioxide is continuously introduced during the carbonation activation process in step (1) to maintain the pH value of the system at 4.0-5.0.

[0014] Preferably, the calcium silicate in step (1) has a particle size of 200 mesh and a purity of not less than 90%.

[0015] Preferably, the mass concentration of the nitric acid aqueous solution in step (2) is 1%.

[0016] Preferably, the triggering liquid is sprayed in step (2) in an atomized manner.

[0017] Preferably, the triggering liquid in step (2) is used to adjust the pH of the system to 7.0-8.0.

[0018] Preferably, the sieving in step (2) is sieved through a 325-mesh sieve.

[0019] Preferably, the acidic silica sol in step (2) is: McLean, model S766406, with a silica content of 30%, an average particle size of 100nm, and a sodium oxide content of <0.1wt%.

[0020] Preferably, the calcium carbonate in step (3) has a dry basis purity of 99.95%-100.05% and a sodium content of no more than 0.01%.

[0021] Preferably, the quartz powder in step (3) is white quartz powder with a particle size greater than 230 mesh.

[0022] Preferably, the alumina in step (3) is α-phase alumina powder, 325 mesh.

[0023] Preferably, the iron oxide particles in step (3) have a particle size of less than 5 μm and a purity of not less than 96%.

[0024] Preferably, the diameter of the raw material ball in step (4) is 10-15 mm.

[0025] Preferably, the specific firing steps in step (5) are as follows: place the raw material balls to be fired in a high-temperature furnace, raise the temperature to 900°C at 10°C / min in an air atmosphere and hold for 20 min, raise the temperature to 1200°C at 5°C / min and hold for 15 min, and then continue to raise the temperature to 1410°C at 5°C / min and hold for 25 min.

[0026] Preferably, the forced air cooling step (5) is to immediately use forced air cooling after the firing is completed, so that the time for the clinker to drop from 1410°C to 1250°C is controlled within 3 minutes, and then continue to cool to below 600°C before taking it out.

[0027] The beneficial effects of this invention are: The calcium-silica-based functional filler provided by this invention has a core layer composed of calcium silicate that has been activated to form an active surface rich in silanol groups. Subsequently, a first silicon source, a second silicon source, and acidic silica sol are sequentially introduced through a stepwise construction method, forming a silanol gradient layer that gradually transitions from the inside to the outside on the surface of the functional filler. This gradient structure allows the functional filler to preferentially adsorb and stably remain near the interface between calcareous and siliceous particles after mixing with raw materials. This provides precisely positioned reaction sites for the subsequent formation of clinker minerals, overcoming the shortcomings of ordinary fillers that are randomly dispersed in raw materials and have difficulty exerting a directional induction effect.

[0028] This invention constructs an intermediate transition layer and a silicon-rich modification layer with a certain thickness and continuity by sequentially adding a first silicon source, a second silicon source, and acidic silica sol. This step-by-step construction method allows for precise control of the density, distribution, and reactivity of silanol groups on the surface of the functional filler. It can participate in the formation of clinker minerals according to the designed rhythm during the heating process, first guiding belite to form fine and uniform crystals at the interface, and then promoting the continuous outward growth of alite from these fine-grained belite. This effectively solves the problems of coarse belite crystals and hindered alite formation under low-alkali conditions.

[0029] After the functional filler is constructed, the present invention uses ammonium bicarbonate triggering liquid for atomized spraying. The rapid increase in pH value enables the surface silicon-oxygen structure to be fixed and stabilized, avoiding the deactivation of surface active sites during subsequent processing and storage.

[0030] This invention atomizes functional fillers into raw materials that have been pre-formed into a thin water film in the form of a suspension, enabling the functional fillers to spread evenly with the water film and migrate to the target interface, thereby further enhancing the effect of its directional distribution at the interface.

[0031] This invention, through a systematic approach from material design to addition method, fully leverages the role of functional fillers. Under the condition of maintaining a low alkali content in clinker, the calcinability of clinker is significantly improved, free calcium oxide is effectively controlled, and the early strength and mid-to-late-stage strength of cement develop in a coordinated manner. Simultaneously, the resistance to sulfate attack and seawater attack is improved, providing more stable low-alkali cement clinker for marine precast components, underground pipe gallery lining, and foundation engineering in high sulfate environments. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0033] The sources or properties of the raw materials used in the embodiments and comparative examples of this invention are as follows: Calcium silicate: Sigma-Aldrich, model 372668, particle size 200 mesh, purity not less than 90%; Tetraethyl orthosilicate: Sigma-Aldrich, model 86578, purity not less than 99.0%; Acidic silica sol: Maclean, model S766406, silica content 30%, average particle size 100nm, sodium oxide content <0.1wt%; Calcium carbonate: Sigma-Aldrich, model 398101, analytical grade, dry basis purity 99.95%-100.05%, sodium content not more than 0.01%; Quartz powder: Sigma-Aldrich, model 83340, white quartz powder, particle size greater than 230 mesh; Alumina: Sigma-Aldrich, model 342688, α-phase alumina powder, 325 mesh; Iron oxide: Sigma-Aldrich, model 310050, particle size less than 5μm, purity not less than 96%.

[0034] Example 1: A method for preparing low-alkali cement clinker, the specific steps of which are as follows: S1: Take 100g of calcium silicate, 200g of anhydrous ethanol and 300g of zirconia balls and add them to a 500mL nylon ball mill jar. Wet ball mill at 280r / min for 4h. After ball milling, pour out the slurry and dry it at 80℃ for 2h. Then pass it through a 325-mesh sieve to obtain pretreated calcium silicate with a median particle size of 2-5μm. Then take 100g of pretreated calcium silicate and add it to 1000g of carbonic acid deionized water pre-adjusted to pH 4 by carbon dioxide bubbling. Stir at 35℃ and 600r / min while continuously introducing carbon dioxide to keep the pH of the system at 4-5. Activate for 20min. After activation, filter immediately and rinse once with carbonic acid deionized water at pH 4 and once with anhydrous ethanol. Keep the wet filter cake. S2: Take all the wet filter cake obtained from S1, 250g of anhydrous ethanol, and 100g of deionized water and add them to a 2L glass reactor. Redisperse the mixture for 15min at 30℃ and 700r / min to obtain a functional filler dispersion slurry. Separately, mix 4g of tetraethyl orthosilicate and 16g of anhydrous ethanol to form the first silicon source solution. Then, mix 5.2g of tetraethyl orthosilicate, 0.6g of tetramethoxysilane, 24g of anhydrous ethanol, and 10g of nitric acid aqueous solution (1%) and let it stand at room temperature for 20min to form the second silicon source solution. First, pulse the first silicon source solution into the high shear zone 20mm below the liquid surface and close to the end of the stirrer within 30s, and continue... Stir for 8 minutes, then add the second silicon source solution at a constant rate from the transition zone 20 mm below the liquid surface and 30 mm from the reactor wall within 20 minutes. After the second silicon source solution is added, slowly add 20 g of acidic silica sol along the inner wall of the reactor within 20 minutes. Separately, dissolve 6 g of ammonium bicarbonate in 80 g of deionized water to form a triggering solution, and spray this triggering solution in a ring along the liquid surface in a misting manner within 2 minutes to adjust the pH value of the system to 7-8. Continue aging for 20 minutes. After aging, filter and wash twice with deionized water and once with anhydrous ethanol. Then dry at 90℃ for 6 hours and pass through a 325-mesh sieve to obtain calcium-silicon based functional filler. S3: Add 784g of calcium carbonate, 37g of aluminum oxide and 25g of iron oxide to a dry mixer. Mix at low speed for 3 minutes, then mix at high speed for 5 minutes to make the lime component and the aluminum and iron correction component form a uniform mixture. Then add 148g of quartz powder and continue to mix at high speed for 2 minutes to obtain a low-alkali raw material matrix. S4: Place 994g of low-alkali raw material matrix in a forced mixer, add 50g of deionized water, and mix at medium speed for 2 minutes to form a continuous but non-flowing thin water film on the surface of calcium carbonate particles, quartz particles, and corrective raw material particles. Add 5g of calcium-silicon-based functional filler to 30g of deionized water and disperse ultrasonically for 5 minutes to obtain a functional filler suspension. Atomize the functional filler suspension into the raw material being mixed within 2 minutes and continue mixing at medium speed for 4 minutes. Then add another 30g of deionized water and continue mixing for 5 minutes to form a wet raw material with a suitable moisture content for pelletizing. Roll the wet raw material into raw material balls with a diameter of 10-15mm and dry them at 105℃ for 4 hours to obtain raw material balls to be fired. S5: Place the raw meal pellets to be fired into a high-temperature furnace, raise the temperature to 900℃ at 10℃ / min in an air atmosphere and hold for 20min to complete the main decomposition reaction of the raw meal, then raise the temperature to 1200℃ at 5℃ / min and hold for 15min, then continue to raise the temperature to 1410℃ at 5℃ / min and hold for 25min. After firing, immediately use forced air cooling to control the time for the clinker to drop from 1410℃ to 1250℃ within 3min, and then continue to cool to below 600℃ and take it out to obtain low-alkali cement clinker.

[0035] Example 2: The difference from Example 1 is as follows: In S1, carbon dioxide is continuously introduced to stabilize the pH of the system at 4.2, and the activation time is 18 min; in S2, the first silicon source solution is prepared by 3.2 g of tetraethyl orthosilicate and 12.8 g of anhydrous ethanol; the second silicon source solution is prepared by 4.4 g of tetraethyl orthosilicate, 0.4 g of tetramethoxysilane, 20 g of anhydrous ethanol and 9 g of nitric acid aqueous solution (1%), wherein tetraethyl orthosilicate and tetramethoxysilane are premixed for 3 min, then nitric acid aqueous solution is added and stirred for 5 min, and then allowed to stand for 15 min; the amount of acidic silica sol added is 16 g; the amount of ammonium bicarbonate added to the trigger solution is 5 g, and the pH of the system after triggering is 7.2; in S3, the amounts of calcium carbonate, quartz powder, alumina and iron oxide added are 770 g, 130 g, 30 g and 20 g, respectively; in S4, the amount of calcium-silicon based functional filler added is 4 g; the remaining conditions are the same as in Example 1.

[0036] Example 3: The difference from Example 1 is as follows: In S1, carbon dioxide is continuously introduced to stabilize the pH of the system at 4.5, and the activation time is 22 min; in S2, the first silicon source solution is prepared by 4.4 g of tetraethyl orthosilicate and 17.6 g of anhydrous ethanol; the second silicon source solution is prepared by 5.0 g of tetraethyl orthosilicate, 0.8 g of tetramethoxysilane, 24 g of anhydrous ethanol and 10 g of nitric acid aqueous solution (1%), wherein tetraethyl orthosilicate and tetramethoxysilane are premixed for 4 min, then nitric acid aqueous solution is added and stirred for 6 min, and then allowed to stand for 16 min; the amount of acidic silica sol added is 22 g; the amount of ammonium bicarbonate added to the trigger solution is 6 g, and the pH of the system after triggering is 7.5; in S3, the amounts of calcium carbonate, quartz powder, alumina and iron oxide added are 800 g, 170 g, 40 g and 30 g, respectively; in S4, the amount of calcium-silicon-based functional filler added is 7 g; the remaining conditions are the same as in Example 1.

[0037] Example 4: The difference from Example 1 is as follows: In S1, carbon dioxide is continuously introduced to stabilize the pH of the system at 4.8, and the activation time is 24 min; in S2, the first silicon source solution is prepared by 4.8 g of tetraethyl orthosilicate and 19.2 g of anhydrous ethanol; the second silicon source solution is prepared by 5.8 g of tetraethyl orthosilicate, 1.0 g of tetramethoxysilane, 26 g of anhydrous ethanol and 12 g of nitric acid aqueous solution (1%), wherein tetraethyl orthosilicate and tetramethoxysilane are premixed for 5 min, then nitric acid aqueous solution is added and stirred for 7 min, and then allowed to stand for 15 min; the amount of acidic silica sol added is 24 g; the amount of ammonium bicarbonate added to the trigger solution is 8 g, and the pH of the system after triggering is 7.8; in S3, the amounts of calcium carbonate, quartz powder, alumina and iron oxide added are 790 g, 162 g, 39 g and 28 g, respectively; in S4, the amount of calcium-silicon based functional filler added is 6 g; the remaining conditions are the same as in Example 1.

[0038] Comparative Example 1: The difference from Example 1 is that after obtaining pretreated calcium silicate in step S1, 100g of pretreated calcium silicate is no longer added to 1000g of carbonated deionized water pre-adjusted to pH 4 by carbon dioxide bubbling for activation, nor is continuous carbon dioxide bubbling, filtration and rinsing performed. Instead, 100g of pretreated calcium silicate is directly used for dispersion and subsequent treatment in step S2, and the other conditions are the same as in Example 1.

[0039] Comparative Example 2: The difference from Example 1 is that in step S2, the first silicon source solution and the second silicon source solution are premixed to form a unified silicon source solution, and added at a constant speed from the transition zone 20 mm below the liquid surface and 30 mm from the vessel wall within 20 min. The step of pulsely adding the first silicon source solution from the high shear zone 20 mm below the liquid surface and close to the end of the stirrer within 30 s is no longer performed. All other conditions are the same as in Example 1.

[0040] Comparative Example 3: The difference from Example 1 is that in step S2, tetramethoxysilane is not added to the second silicon source solution, but is replaced by an equal amount of tetraethyl orthosilicate. The other conditions are the same as in Example 1.

[0041] Comparative Example 4: The difference from Example 1 is that in step S2, the acidic silica sol is no longer slowly added along the inner wall of the reactor. Instead, the acidic silica sol is pre-mixed with the second silicon source solution and then added at a constant rate from the transition zone 20 mm below the liquid surface and 30 mm from the reactor wall within 20 min. The other conditions are the same as in Example 1.

[0042] Comparative Example 5: The difference from Example 1 is that in step S2, the second silicon source solution is first pulsedly added from the high shear zone 20 mm below the liquid surface and close to the end of the stirrer within 30 seconds, and stirring is continued for 8 minutes. Then, the first silicon source solution is uniformly added from the transition zone 20 mm below the liquid surface and 30 mm from the reactor wall within 20 minutes. After the first silicon source solution is added, the acidic silica sol is slowly added along the inner wall of the reactor. The other conditions are the same as in Example 1.

[0043] Comparative Example 6: The difference from Example 1 is that ammonium bicarbonate triggering solution is not added in step S2, but is replaced by an equal amount of deionized water. The other conditions are the same as in Example 1.

[0044] Comparative Example 7: The difference from Example 1 is that in step S4, the calcium-silicon-based functional filler is not added to deionized water to form a functional filler suspension and then atomized and sprayed in. Instead, after the low-alkali raw material matrix obtained in step S3 is prepared, the calcium-silicon-based functional filler is directly added to the low-alkali raw material matrix and dry-mixed for 2 minutes. The other conditions are the same as those in Example 1.

[0045] Performance testing The low-alkali cement clinker samples obtained in Examples 1-4 and Comparative Examples 1-7 were used for performance testing, as detailed below: Clinker chemical composition and alkali equivalent: The analysis was conducted according to GB / T 176-2017 "Cement Chemical Analysis Methods". Each low-alkali cement clinker sample was taken, quartered, and ground until all particles passed through an 80μm square-hole sieve. The mass fractions of Na2O, K2O, CaO, SiO2, Al2O3, and Fe2O3 were determined, and the alkali equivalent was calculated according to Na2Oeq = Na2O + 0.658K2O (wherein, when the K2O content is lower than the detection limit (LOD) of the method, the LOD is 0.01%). Clinker free calcium oxide: The analysis was conducted according to GB / T 176-2017 "Cement Chemical Analysis Methods". Each low-alkali cement clinker sample was ground until it passed through an 80μm square mesh sieve. Two parallel samples of 0.5000g each were weighed and the free calcium oxide content was determined according to the standard method. The test results are shown in Table 1.

[0046] Application performance test: Each low-alkali cement clinker sample was first crushed to a particle size of less than 5mm by a jaw crusher, and then ground together with dihydrate gypsum at a mass ratio of 95:5 for low-alkali cement clinker sample: dihydrate gypsum. Each test item was tested in parallel at least 3 times, and the average value was taken as the result. Standard consistency water requirement and setting time: Refer to GB / T 1346-2024 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". Use the aforementioned cement samples and determine the standard consistency water requirement, initial setting time and final setting time using a Vicat apparatus. Cement mortar strength: The strength of cement mortar was tested according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". 40mm×40mm×160mm mortar specimens were prepared using the aforementioned laboratory cement samples. Each group consisted of 450g cement, 1350g standard sand, and 225g water. After molding, the specimens were cured for 24 hours at 20.0℃ and relative humidity not less than 90%. After demolding, they were placed in water at 20.0℃ and cured for 3 days and 28 days, respectively. The flexural strength and compressive strength were then determined. Sulfate erosion resistance: The K method of GB / T 749-2008 "Test Method for Sulfate Erosion Resistance of Cement" was used. The aforementioned cement samples were used to prepare mortar specimens according to the standard and divided into a water-cured control group and a sulfate erosion group. After curing under the standard conditions for 56 days, the flexural strength was measured, and the sulfate erosion resistance coefficient K was calculated according to the ratio of the flexural strength of the erosion group to that of the water-cured control group. Seawater erosion resistance: The test was conducted in accordance with GB / T 38140-2019 "Test Method for Seawater Erosion Resistance of Cement". Mortar specimens were prepared using the aforementioned cement samples. After demolding, the specimens were first cured in water at 50℃ for 7 days. They were then divided into a water-cured control group and a simulated seawater wet-dry cycle group. The compressive strength was measured after 90 days of testing. The seawater erosion resistance coefficient Ksw was calculated based on the ratio of the compressive strength of the simulated seawater group to that of the water-cured control group. The test results are shown in Table 2.

[0047] Table 1. Clinker chemical composition, alkali equivalent, and free calcium oxide test data

[0048] Table 2 Application Performance Testing Standards

[0049] Data Analysis: As can be seen from the data in the examples in the table, the free calcium oxide in the low-alkali cement clinker prepared by the present invention first decreases and then tends to balance as the degree of calcium-silicon-based functional filler construction is optimized, while the alkali equivalent remains low and changes little. The 3-day strength, 28-day strength, and resistance to sulfate and seawater corrosion are synergistically improved. This indicates that the scheme does not simply rely on increasing the silicon source, but rather on the continuous combination of restricted decalcification activation, two-stage molecular silicon source, acidic silica sol, and ammonium bicarbonate triggering liquid, which makes it easier for the functional filler to be directionally distributed at the interface between calcareous particles and silica particles. This simultaneously takes into account the scalability under low-alkali conditions, the mid-to-late-stage strength development, and the service stability under seawater and sulfate environments. It is more suitable for marine precast components, underground pipe gallery lining, and foundation engineering in high-sulfate environments.

[0050] As can be seen from the data in Table 1 for Example 1 and Comparative Example 1, after the restricted decalcification activation under continuous carbon dioxide maintenance was removed, the free calcium oxide, standard consistency water consumption, and setting time all changed in an unfavorable direction, and the strength and erosion resistance decreased simultaneously. The main reason is that it is difficult for a sufficient number of uniform silanol sites to form on the surface of the pretreated calcium silicate, which weakens the orientation effect of the functional filler in the raw material.

[0051] As can be seen from the data in Example 1 and Comparative Example 2 in Table 1, after the first and second silicon sources were pre-mixed and added together, the free calcium oxide was the highest, and the strength and corrosion resistance indicators decreased the most significantly. The main reason for this is that the original temporal difference was weakened, making it difficult for the functional filler surface to first form an inner layer closely adhering to the activation site, and then form a relatively outer continuous extension layer. Furthermore, the subsequent addition of acidic silica sol also made it difficult to clearly differentiate its function from the first two steps. This result indicates that the first and second silicon sources are not simply additive; rather, only when they are introduced separately in a predetermined order and spatial position can they produce an interface-induced effect significantly greater than the sum of a single step.

[0052] As can be seen from the data in Table 1 for Example 1 and Comparative Examples 3 and 4, when tetramethoxysilane is not added to the second silicon source, or when the acidic silica sol is mixed with the second silicon source before being added together, the mid-to-late-stage strength and erosion resistance of the samples all show varying degrees of decline. The main reason is that the second silicon source is supposed to play a role in the slow-release and extension of the rapid site-occupancy result of the first silicon source, while the acidic silica sol is more suitable for forming a relatively outer silicon-rich layer afterward. When the former lacks tetramethoxysilane, the reaction rhythm and layering of the molecular silicon source are weakened; if the latter is mixed in advance, it will weaken the gradient characteristics of gradual enrichment from the inside out. This indicates that there is a synergistic relationship between the composition design of the second silicon source and the location of the addition of the acidic silica sol; only through their synergy can the surface silanol gradient layer be more complete.

[0053] As can be seen from the data in Table 1 for Example 1 and Comparative Examples 5 and 6, once the order of the first and second silicon sources is disrupted, or the ammonium bicarbonate trigger solution is removed, the free calcium oxide, stability, and corrosion resistance of the samples all deteriorate significantly, and this deterioration is not limited to a single indicator. The main reason is that the three processes form a continuous process that is interconnected and interdependent. If the order is reversed, or the subsequent trigger is missing, the spatial differences established earlier are difficult to fix, and the correspondence between the functional filler surface and the raw material particle contact interface is weakened.

[0054] As can be seen from the data in Table 1 for Example 1 and Comparative Example 7, even if the calcium-silica-based functional filler itself has been prepared, if it is not sprayed in as a suspension atomization in the final stage of raw material mixing, but instead directly dry-mixed, the free calcium oxide, strength, and erosion resistance of the samples will still decrease overall. The main reason is that the thin water film formed after pre-wetting provides more favorable adhesion and migration conditions for the functional filler, causing it to preferentially distribute at the interface between calcareous and siliceous particles; direct dry mixing, on the other hand, is more likely to result in random dispersion, making it difficult to fully demonstrate the advantages of the functional filler in interface induction. This result indicates that the presence of the functional filler is just as important as its introduction method. Only when the material design and the addition path are matched simultaneously can the unpredictable synergistic effect of this invention in low alkali, easy burning, and mid-to-late-stage strength development be fully realized.

[0055] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A low-alkali cement clinker, characterized in that, The low-alkali cement clinker is obtained by firing the following raw materials by mass: 770-800 parts calcium carbonate, 130-170 parts quartz powder, 30-40 parts alumina, 20-30 parts iron oxide and 4-7 parts calcium-silicon-based functional filler. The calcium-silicon-based functional filler consists of pretreated calcium silicate and a silanol gradient layer coating the surface of the pretreated calcium silicate. Based on 100 parts of the pretreated calcium silicate, the silanol gradient layer is formed by sequentially treating a first silicon source, a second silicon source, an acidic silica sol, and an ammonium bicarbonate trigger solution; the first silicon source is formed by mixing 3.2-4.8 parts of tetraethyl orthosilicate and 12.8-19.2 parts of anhydrous ethanol; the second silicon source is formed by mixing 4.4-5.8 parts of tetraethyl orthosilicate, 0.4-1.0 parts of tetramethoxysilane, 20-26 parts of anhydrous ethanol, and 9-12 parts of a 1% (w / w) aqueous solution of nitric acid; the amount of the acidic silica sol is 16-24 parts.

2. The low-alkali cement clinker according to claim 1, characterized in that, Based on 100 parts of the pretreated calcium silicate, the amount of ammonium bicarbonate used is 5-8 parts.

3. The low-alkali cement clinker according to claim 1, characterized in that, The pretreated calcium silicate is obtained by ball milling calcium silicate and then activated by carbonated deionized water.

4. A method for preparing low-alkali cement clinker according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Calcium silicate is wet-milled to form pretreated calcium silicate, and the pretreated calcium silicate is dispersed in carbonated deionized water for carbonation activation treatment. After filtration and washing, a wet filter cake is obtained. (2) Disperse the wet filter cake obtained in step (1) in a mixed solvent to form a functional filler dispersion slurry; add the first silicon source, the second silicon source and acidic silica sol in sequence, and finally spray in the triggering liquid for aging to obtain calcium-silicon based functional filler; (3) Mix calcium carbonate, aluminum oxide, iron oxide and quartz powder to obtain a low-alkali raw material matrix; (4) The calcium-silicon functional filler is sprayed into the low-alkali raw material matrix to form wet raw material, and rolled into raw material balls. After drying, the raw material balls to be fired are obtained. (5) The raw material balls to be fired are heated in stages under an air atmosphere and then forced to cool after firing to obtain low-alkali cement clinker.

5. The preparation method according to claim 4, characterized in that, The pH value of the carbonated deionized water in step (1) is 4.0-4.8; carbon dioxide is continuously introduced during the carbonation activation process to keep the pH value of the system at 4.0-5.

0.

6. The preparation method according to claim 4, characterized in that, The triggering solution described in step (2) is used to adjust the pH of the system to 7.0-8.

0.

7. The preparation method according to claim 4, characterized in that, The diameter of the raw material balls mentioned in step (4) is 10-15 mm.

8. The preparation method according to claim 4, characterized in that, The specific firing steps in step (5) are as follows: place the raw material balls to be fired in a high-temperature furnace, raise the temperature to 900°C at 10°C / min in an air atmosphere and hold for 20 min, raise the temperature to 1200°C at 5°C / min and hold for 15 min, and then continue to raise the temperature to 1410°C at 5°C / min and hold for 25 min.

9. The preparation method according to claim 4, characterized in that, The specific steps of forced air cooling in step (5) are as follows: immediately after the firing is completed, forced air cooling is used to control the time for the clinker to drop from 1410℃ to 1250℃ within 3 minutes, and then continue to cool it to below 600℃ before taking it out.